2005
DOI: 10.1128/jvi.79.17.11259-11268.2005
|View full text |Cite
|
Sign up to set email alerts
|

CD46-Utilizing Adenoviruses Inhibit C/EBPβ-Dependent Expression of Proinflammatory Cytokines

Abstract: The majority of adenovirus serotypes utilize the coxsackievirus-adenovirus receptor (CAR) for virus-host cell attachment, but subgroup B and subgroup D (adenovirus type 37 [Ad37]) viruses recognize CD46. CD46 is a ubiquitously expressed receptor that serves as a cofactor for the inactivation of the complement components C3b and C4b, and it also serves as a receptor for diverse microbial pathogens. A reported consequence of CD46 engagement is a reduced capability of human immune cells to express interleukin-12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 66 publications
0
27
1
Order By: Relevance
“…Ad-36 reduced MCP-1 expression in explants, but Ad-19 increases MCP-1 expression (62) and Ad-7 increases interleukin-8 production (63). On the other hand, adenovirus types 16, 35, and 37 reduce proinflammatory cytokine expressions (64). Interestingly, Ad-37 is reported to increase adiposity in animals (33).…”
Section: Discussionmentioning
confidence: 99%
“…Ad-36 reduced MCP-1 expression in explants, but Ad-19 increases MCP-1 expression (62) and Ad-7 increases interleukin-8 production (63). On the other hand, adenovirus types 16, 35, and 37 reduce proinflammatory cytokine expressions (64). Interestingly, Ad-37 is reported to increase adiposity in animals (33).…”
Section: Discussionmentioning
confidence: 99%
“…46 For PBMCs and plasmacytoid DCs different responses to CAR-binding and CD46-binding adenoviruses have been reported. 54,55 Clearly, differences between adenovirus serotypes with respect to how they affect DCs and more generally strategies for directed modulation of DC functions by adenovirus capsid modification need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Adenovirus vectors were propagated in 293 cells as previously described (22). Ad5.F16 empty capsids (EC), produced during normal viral propagation, were readily purified from mature particles on CsCl gradients due to an approximate 1.5-cm distance separating the two viral species.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies showed that infection of human PBMC by the CD46-utilizing Ads Ad37, Ad16, and Ad35 leads to an impairment in cytokine production (22). CD46 Ads, but not the CAR-utilizing Ad5, interfere with gamma interferon signaling events in monocytes that are necessary for expression of the C/EBP␤ transcription factor, which in turn is required for subsequent proinflammatory cytokine gene transcription.…”
mentioning
confidence: 99%